COMPUTER AIDED ARTICULATORY TUTOR: A SCIENTIFIC STUDY - Rathinavelu, Arumugam; Thiagarajan, Hemalatha (International Journal of Computing, 2014)
This paper describes the use of Computer Aided Articulation Tutor (CAAT) to conduct phonetic training to the hearing-impaired (HI) children with inner articulators as visual cues. This Articulatory tutor was developed by using Magnetic Resonance Imaging (MRI) and computer graphics techniques. The articulators include the movement of jaw, lips, tongue and velum. Ten hearing impaired (HI) children between the ages 4 and 7 were selected and trained for 10 hours across 4 weeks on 24 words. Intelligibility of HI children was investigated to find out their performance in speech perception and articulation. The post-training results indicated that HI children improved in articulation of speech sounds placed at different contexts. This 3D visual simulation tool helped HI children in perceiving the speech information significantly.